How Comfortable Are You Really? A Qualitative Analysis of Teacher Candidates Perceptions of Their Comfortability with Diverse Populations - Kohler, Patricia; Slaton, Chayla; Wingfield, Rachel; Barnes, Candice; Ward, Ashley (Advances in Social Sciences Research Journal, 2020)
In an increasingly diverse school population, teachers find themselves facing students whose ethnicities, cultures, experiences, and religions are vastly different from their own. While this is a fantastic opportunity to develop a unique learning community, it is also challenging for teachers who may or may not have adequate training to meet the needs of all students. Using a survey designed to determine how comfortable an individual is in a variety of situations characterized by diversity, pre-service education candidates from the Elementary K-6 and Special Education K-12 degree programs from a mid-sized university in Arkansas were given a questionnaire on their comfortability with different diversity characteristics. The semester in which participants engaged in this survey included field placement. Results from the questionnaire indicated that the lowest average comfortability rating was for the HIV category, and the highest average comfortability rating was for the disability category. Qualitative information suggests that pre-service teachers perceive that they are "comfortable" with different groups of people, although previous research cautions against this comfortability. The authors suggest that teacher education programs, professional development, and staff in-service training on diversity topics should consider several practices designed to bolster how teacher candidates prepare to work with diverse populations of students. Keywords: teacher candidates, diversity, perceptions, comfortability